Hukum menikahi wanita hamil sebab zina perspektif 4 mazhab - Al Haqiqy, Muhammad Sirajuddin (Maliki Interdisciplinary Journal, 2025)
This article discusses marriage in Islam as an act of worship that carries important wisdom, such as fulfilling biological needs, maintaining personal purity, and building a harmonious family. Based on the Qur'an and Hadith, marriage is permitted, recommended, or obligatory under certain conditions, such as to avoid committing zina (unlawful sexual relations). The differences in scholars' opinions regarding the laws of marriage highlight the flexibility of Islamic law in accommodating individual circumstances. Furthermore, this article examines the legal status of marriage with a pregnant woman as a result of zina from the perspectives of the four major schools of Islamic jurisprudence (mazhab) and explores the status of a child born as a result of zina, who is only to be attributed to the mother, with the consequence of no legal mahram relationship or inheritance rights. Overall, this article provides an understanding of the laws governing marriage, the case of a woman pregnant due to zina, and its legal consequences in Islam.